Debris Flow Simulation for Dam Safety Assessment in Malaysia - Wahab W.A.; Aripin M.F.S.M.; Jaapar A.R.; Omar R.C.; Isa A.A.M.; Ali A.; Zakaria M.S.; Roslan R.; Taher T.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Debris and mud floods are the last stages in the overall debris flow process. This event occurred in multiple catchments around Gunung Jerai on the 18th of August 2023, leading to floodingin several parts of the Yan Districtwhich situated to the west of Gunung Jerai. The debris flow disasters in Seri Perigi Catchment, Titi Hayun Catchment, and Batu Hampar Catchment show the consequences of natural temporary dam breaches resulting from two geomorphological setting: temporary landslide dams and narrow river mouth due to topography. This study used modelling and simulationtechniques to compute the debris flows volume, velocity, momentum, and pressure resulting from the geological disaster. Debris flow simulationrevealed a total volume of 64,364.69 m3 debris was recorded in the Seri Perigi Catchment area, 642,596.60 m3 total volume in the Titi Hayun Catchment, and 595,632.89 m3 total volume of debris flow in the Batu Hampar Catchment. The average velocity of this debris flow is between 12.90m/s and 18.75m/s with an average momentum between 20.96 kgm/s and 109.07 kgm/s. The field mapping, modelling, and simulation outcomes indicate significant geological events related to debris flow occurin Seri Perigi Catchment, Titi Hayun Catchment, and Batu Hampar Catchment. In contrast, other catchments faced comparatively minor debris flow or extreme water surge phenomena. With these simulations, it is possible to assess the potential future risks of geological disasters caused by debris flow and pinpoint the optimal location for the Sabo Dam. This information can greatly assist local authorities in devising and implementing both structural and non-structural mitigation plans. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.